Why do people file share unlawfully? A systematic review, meta-analysis and panel study. (July 2017) - Fleming, Piers; Watson, Steven J.; Patouris, Elisavet; Bartholomew, Kimberley J.; Zizzo, Daniel J.
Abstract: Unlawful digital media sharing is common and believed to be extremely damaging to business. Understanding unlawful file sharers' motivations offers the opportunity to develop business models and behavioral interventions to maximize consumers' and businesses' benefit. This paper uses a systematic review of unlawful file sharing research, and the Theory of Planned Behavior, to motivate a large-scale panel study in which initial determinants were used to predict subsequent behavior. A meta-analysis found Attitudes, Subjective Norms and Perceived Behavioral Control were all associated with unlawful file sharing. Media type and demographic differences in the importance of Perceived Behavioral Control were found and attributed to more accurate evaluation of familiar activities, i.e., greater experience increases the influence of Perceived Behavioral Control but age does not. The panel study confirmed that greater past experience was associated with Perceived Behavioral Control and Intention. We conclude that past experience increases the efficacy of the Theory of Planned Behavior and specifically Perceived Behavioral control in predicting behavior, contrary to some widely held beliefs about the role of experience. The role of experience is therefore crucial to understanding people's choices. Practically, improving social approval, positive evaluation and access to lawful media should reduce unlawful behavior. Highlights: Theory of Planned Behavior research on unlawful file sharing was meta-analyzed. Attitude, Subjective Norms and Perceived Behavioral Control (PBC) were predictive. PBC was more predictive of intention to file share for music and students. A panel study tested if past experience explains better PBC-intention prediction. Past experience was associated with PBC and intention to unlawfully download music.